Fracture Reduction and Fixation Techniques Upper Extremities (Springer International Publishing, 2018)
In this highly illustrated book, the techniques of fracture reduction are clearly demonstrated using a step-wise approach with real time intra-operative photographs. Tips and tricks for how to avoid pitfalls are presented by a panel of experts and all upper extremity anatomical sites are included to give the readers a complete overview of how to perform reduction techniques for different fracture types. This book will be an essential guide for surgeons to utilise the available reduction instruments and preserve the vitality of the surrounding soft tissues and bone.